Uukuniemi virus infection causes a pervasive remodelling of the RNA-binding proteome in tick cells - Wilson, Alexandra; Kamel, Wael; Davies, Kelsey; De Laurent, Zaydah R; Arif, Rozeena; Clarke, Andrew T; Bell-Sakyi, Lesley; Lamont, Douglas; Demyanenko, Yana; Noerenberg, Marko; Kohl, Alain; Mohammed, Shabaz; et al. (PLoS pathogens, 2025)
Cellular RNA-binding proteins (RBPs) are pivotal for the viral lifecycle, mediating key host-virus interactions that promote or repress virus infection. While these interactions have been largely studied in the vertebrate host, no comprehensive analyses of protein-RNA interactions occurring in cells of arbovirus vectors, in particular ticks, have been performed to date. Here we systematically identified the responses of the RNA-binding proteome (RBPome) to infection with a prototype bunyavirus (Uukuniemi virus; UUKV) in tick cells and discovered changes in RNA-binding activity for 283 proteins. In an orthogonal approach, we analysed the composition of the viral ribonucleoprotein by immunoprecipitation of UUKV nucleocapsid protein (N) in infected cells. We found many tick RBPs that are regulated by UUKV infection and associate with viral nucleocapsid protein complexes, and we confirmed experimentally that they impact UUKV infection. This includes the tick homolog of topoisomerase 3B (TOP3B), a protein able to manipulate the topology of RNA, which particularly affected viral particle production. Our data thus reveals the first protein-RNA interaction map for infected tick cells.
Keywords: proteom; Orthobunyavirus; Ticks; Host-Pathogen Interactions; Nucleocapsid Proteins; klíšťata; infekce viry z čeledi Bunyaviridae; Animals; Proteome; nukleokapsida - proteiny; Bunyaviridae Infections; interakce hostitele a patogenu; RNA-Binding Proteins; zvířata; proteiny vázající RNA